Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

Building Integrated Software Development Environments, Part I: Tool Specification - Engels, Gregor; Lewerentz, Claus; Nagl, Manfred; Schäfer, Wilhelm; Schürr, Andy (ACM Transactions on Software Engineering and Methodology (TOSEM))
The conceptual modeling approach of the IPSEN (Integrated Project Support Environment) project for building highly integrated environments is based on using attributed graphs to model and implement arbitrary object structures, in particular all kinds of software documents and their relationships. A language based on graph grammars, called PROGRESS (Programmed Graph REwriting SyStems), and a suitable method for the application of this language, called graph grammar engineering, have been developed over the last ten years. This language and method are being extensively used for specifying the complex graph structures of internal document representations as well as for specifying the functionality of all tools (editors, browsers, analyzers, debuggers) working on these internal representations. This paper explains the language and the method for applying the language based on a pragmatic nontrivial example of a software production process and its corresponding documents. In particular, it is shown why and how a graph grammar-based strongly typed language is perfectly suitable to formally specify highly integrated software tools. In addition, it is shown that the implementation of these tools (i.e., an environment composed of these tools) is systematically being derived from the formal specifications.

FRESCO: The French Telephone Speech Data Collection - Part of the European SpeechDat(M) Project - Langmann, Detlev; Haeb-Umbach, Reinhold (ICSLP, Philadelphia)
The paper describes the design, collection and postprocessing of the French SpeechDat corpus FRESCO. Being a database of approximately 35000 utterances recorded from 1000 callers over the terrestrial telephone network in France, it comprises immediately usable and relevant speech for the initial training and assessment of speaker independent phoneme model or word model based speech recognizers, as they are employed in automated telephone services. FRESCO is one of the 1000 speaker telephone speech databases produced as "case studies" within the European project SpeechDat(M).

The MOL Project: An Open, Extensible Metacomputer - Reinefeld, Alexander; Baraglia, Ranieri; Decker, Thomas; Gehring, Jörn; Laforenza, Domenico; Ramme, Friedhelm; Römke, Thomas; Simon, Jens (Proc. Heterogenous Computing Workshop (HCW))

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).

European Speech Databases for Telephone Applications - Hoege, H.; Tropf, H. S.; Winsky, R.; van den Heuvel, H.; Haeb-Umbach, Reinhold; Choukri, K. (ICASSP, Munich)
The SpeechDat project aims to produce speech databases for all official languages of the European Union and some major dialectal variants and minority languages resulting in 28 speech databases. They will be recorded over fixed and mobile telephone networks. This will provide a realistic basis for training and assessment of both isolated and continuous-speech utterances, employing whole-word or subword approaches, and thus can be used for developing voice driven teleservices including speaker verification. The specification of the databases has been developed jointly, and is essentially the same for each language to facilitate dissemination and use. There will be a controlled variation among the speakers concerning sex, age, dialect, environment of call, etc. The validation of all databases will be carried out centrally. The SpeechDat databases will be transferred to ELRA for distribution. The next databases to be recorded will cover East European languages.

Towards Quality of Service for Parallel Computing: An Overview of the MILAN Project - Karl, Holger (High-Performance Computing and Networking, 7th International Conference, HPCN Europe 1999, Amsterdam, The Netherlands, April 12-14, 1999, Proceedings)

Formal Integration of Software Engineering Aspects Using Graph Rewrite Systems - A Typical Experience?! - Engels, Gregor; Zamperoni, Andreas (Proceedings of the International Workshop on Applications of Graph Transformations with Industrial Relevance (AGTIVE 1999), Kerkrade (The Netherlands))
This position paper weighs the benefits against the problems of using a graph rewrite system for the formal specification of an integrated software engineering model and for its implementation using the same graph rewrite system. The integrated software engineering approach, called GRIDS1, has been motivated by the shortcomings of software engineering support for real-life software projects. It is based on the formal integration of software engineering aspects for the automatic construction and well-defined manipulation of situational project frameworks. GRIDS uses the graph rewrite system PROGRES for the formal specification of the concepts and for their prototypical implementation. Without claiming to cover the entire field of graph rewrite systems, the experiences of this particular, graph-based approach are used as example for a discussion about the adequacy, the benefits, but also the shortcomings and the problems of applying a graph rewrite approach to realize automated software and method engineering support.

State of the art and development trends of ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics Symposium, 2000 IEEE)
Ultrasonic linear motors have now been investigated for several years. Their key features are high thrust forces related to their volume and good position-accuracy. This contribution consists of two main parts. In the first part we describe the state-of-the-art of linear piezoelectric motors. Characteristics like no-load velocity, maximum thrust force and other technical properties of commercially available devices will be reported as well as those of prototypes. In the second part we report an ongoing research and development project aiming at a linear piezoelectric motor, which is capable of surpassing some of the shortcomings of other piezoelectric motors
Keywords: linear motors; ultrasonic motors; linear piezoelectric motor; maximum thrust force; no-load velocity; ultrasonic linear motor; Electromagnetic devices; Electromagnetic fields; Frequency; Friction; Gears; Materials science and technology; Piezoelectric materials; Research and development; Vibrations; Wheels

Open Petri Nets as Semantic Model for Business Process Integration - Heckel, Reiko (Proceedings of the 2nd International Colloquium on Petri Net Technologies for Modelling Communication Based Systems)
One important application of Petri nets is thespecification of workflows. Such a specification is needed, for example, when interoperability of the workflows is an issue, which is frequently the case when business processes of different organizations shall be integrated.A workflow net is a Petri net satisfying some structural constraints, like the existence of one initial and one final place, and a corresponding soundness condition.An interorganizational workflow is modeled as a set of such workflow nets connected through additional places for asynchronous communication and synchronization requirements on transitions.In this contribution we interpret an interorganizational workflow as acomposition of open nets. This allows us to project processes of the overall net to open processes of the local nets and,vice versa, to deduce the global behavior from the behavior of the components.Such a compositional uunderstanding of workflows can be used to simulate and test local workflow nets in an unknown environment, and it provides the semantic justification for reusable components.